2020
DOI: 10.3390/nu13010039
|View full text |Cite
|
Sign up to set email alerts
|

Regular Use of VKA Prior to COVID-19 Associated with Lower 7-Day Survival in Hospitalized Frail Elderly COVID-19 Patients: The GERIA-COVID Cohort Study

Abstract: Background. Vitamin K concentrations are inversely associated with the clinical severity of COVID-19. The objective of this cohort study was to determine whether the regular use of vitamin K antagonist (VKA) prior to COVID-19 was associated with short-term mortality in frail older adults hospitalized for COVID-19. Methods. Eighty-two patients consecutively hospitalized for COVID-19 in a geriatric acute care unit were included. The association of the regular use of VKA prior to COVID-19 with survival after 7 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…For example, a recent study concluded that prior use of therapeutic anticoagulation was not associated with improved survival in hospitalized COVID-19 patients [ 39 ]. Similarly, a small study found that regular VKA use in hospitalized frail older patients with COVID-19 was associated with increased mortality during the first week [ 40 ]. On the contrary, a retrospective study concluded that COVID-19 patients on OAC at the time of infection and throughout their disease course had significantly lower risk of all-cause mortality at 21 days [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study concluded that prior use of therapeutic anticoagulation was not associated with improved survival in hospitalized COVID-19 patients [ 39 ]. Similarly, a small study found that regular VKA use in hospitalized frail older patients with COVID-19 was associated with increased mortality during the first week [ 40 ]. On the contrary, a retrospective study concluded that COVID-19 patients on OAC at the time of infection and throughout their disease course had significantly lower risk of all-cause mortality at 21 days [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase observed in GAS6 underlines the importance of the vitamin K status in COVID-19. Interestingly, increased uncarboxylated matrix Gla protein has been detected in COVID-19 patients with poor outcomes [25], and regular use of oral antivitamin K anticoagulants prior to COVID-19 is associated with lower survival in elderly patients [26]. A poor vitamin K status could decrease the vitamin K-dependent actions of GAS6 and the anticoagulant PROS1, among other effects [27].…”
Section: Figure 5 Axl Inhibition Reduced Cytokine Production Upon Lps Challenge In Activated Human Macrophages (Thp-1 Cells)mentioning
confidence: 99%
“…The Role of Complementary and Alternative Medicines in the Treatment and Management... DOI: http://dx.doi.org/10.5772/intechopen.100422 that vitamin K antagonist regular use was correlated with augmented mortality in hospitalized elderly patients affected with COVID-19 [86].…”
Section: Nutritional Supplementsmentioning
confidence: 99%